2006
DOI: 10.1345/aph.1g485
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety and Quality Improvement Act of 2005

Abstract: The Act protects clinicians who report minor errors to PSOs and protects the information from disclosure, but providers must increasingly embrace a culture of interdisciplinary concern for patient safety if this protection is to have real impact on patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…[ 4 ] Safety culture differed significantly not only between hospitals but also within the institutions. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Safety culture differed significantly not only between hospitals but also within the institutions. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that nurses, doctors, and managers are unwilling to challenge poor performance. Although British [9] and American [10] governments have published documents to protect "whistleblowers," these may provide inadequate protection [11]. A recent survey by the British Medical Association found that three quarters of 565 doctors surveyed had, at some stage in their career, harbored concerns about a colleague.…”
Section: Performance Monitoring By Local Peers Is Unrealisticmentioning
confidence: 99%
“…This legislation provides confidentiality to medical error reports that are voluntarily made to accredited patient safety organizations. Patient safety organizations analyze these reports and provide feedback on how to improve the delivery of healthcare [43]. This law should improve healthcare quality, because information provided by "near misses" can protect patients from future serious harm.…”
Section: How Patient Safety Is Being Improved In the United Statesmentioning
confidence: 99%